Olive Oil‐Based Ultrafine Theranostic Photo Nanoemulsions: A Versatile Tumor Maneuvering Nanoplatform for Precise Controlled Drug Release in Tumor and Complete Tumor Eradication Mediated by Photo‐Chemotherapy. Issue 6 (12th March 2019) - Rejinold, N. Sanoj; Cherukula, Kondareddy; Ha, Jong Hoon; Park, In‐Kyu; Kim, Yeu‐Chun
Abstract: Photothermal therapy (PTT) is an efficient approach to treat tumors. However, heterogeneous distribution of heat by PTT in the tumor region often results in tumor regrowth and metastasis. Integrating PTT with chemotherapy in a precisely controlled tumor maneuvering and drug‐releasing nanoconstruct will be an ideal strategy for higher therapeutic index. Herein, nanoemulsions (NEMSn) based on a highly biocompatible extra virgin olive oil are developed to encapsulate IR‐780 for PTT and near infrared fluorescence imaging as well as doxorubicin (DOX) for chemotherapy. NEMSn are further stabilized with Tween‐20 and hyaluronic acid to form an ultrafine theranostic photo nanoemulsions (UTPNEMSn) for combinatorial photo‐chemotherapy. Once injected into the system, UTPNEMS homes to the tumor region owing to passive targeting. Tumor accumulated UTPNEMSn readily destabilizes upon laser irradiation to release the DOX, thereby synergizing the therapeutic effects of DOX and PTT. In vivo studies demonstrate a complete tumor eradication without tumor recurrence or systemic toxicity, owing to their biocompatible formulation. By virtue of the olive oil based NEMSNs and precise controlled drug releasing properties collaborating with the synergistic therapeutic modalities, UTPNEMSn are able to provide a promising method for controlled drug delivery systems. Abstract : A novel drug delivery system in nanoemulsions is developed, which is based on a highly biocompatible extra virgin olive oil to encapsulate IR‐780 for photothermal therapy and near infrared fluorescence imaging as well as the doxorubicin for chemotherapy. It shows precise and controlled drug releasing properties collaborated with the synergistic therapeutic modalities.